Direct Cash Assistance of Village Funds in Arjowilangun, Malang District: an Evaluation Approach - apriyanto Romadhan; Iradhad Taqwa Sihidi; Deva Cahya Anestasya (Department of Public Administration, 2023)
Village Fund Direct Cash Assistance (BLT DD) is assistance specifically for people affected by the Covid-19 Pandemic, especially for the poor. Evaluation of the Village Fund BLT management is needed to avoid fraud because it relates to the community. Village Fund Direct Cash Assistance (BLT DD) comes from the Village Fund. This research aims to find out how evaluation of the Management of Direct Village Fund Cash Assistance (BLT DD) During a Pandemic in Arjowilangun Village, Kalipare Malang Regency, in 2021. Researchers used descriptive, qualitative methods with data collection techniques using observation, interviews, and documentation. The subjects of this study were the coordinator of the Village Fund BLT data collection officer for COVID-19/welfare, the Village Fund BLT data collection officer, and some of the community recipients of the Village Fund BLT in Arjowilangun Village. Using evaluation indicators, according to William N. Dunn, are effectiveness, efficiency, adequacy, responsiveness, responsiveness, and alignment. The results of this study indicate that the management of Village Fund BLT in Arjowilangun Village for data collection on Village Fund BLT recipients is in accordance with the specified mechanism. However, there are indications that BLT Village Fund recipients will receive other assistance